Young people between places: (im)mobilities and identifications of young students from rural schools and urban edges in Entre Ríos (PAMPA, 2025)
We analyze the spatial (im)mobilities and identifications of young students in territories of the province of Entre Ríos based on the exchange between two ethnographies: one, carried out with secondary students from the “mountain school” attended by those who live in the rural area and students residing in the nearest city; the other, in the “edge school”, in a peri-urban area, attended by young people from the same neighborhood and surrounding neighborhoods as well as from horticultural families who live nearby. We point out that youth experiences are related to the “between” the different territories that are (re)configured through these experiences of (im)mobilities: between the countryside and the city; between the neighborhood, the center and the horticulture zone, while young people build identifications and alterities based on dichotomous and essentializing constructions of the rural and the urban.
Keywords: Young people; (Im)mobilities; Secondary school; Identifications; Ruralities